«Methodological challenges in the study of political elites. Some reflections from Southern Europe» - Freire, A.; Coller, X.; Ioannis Andreadis; Antonio M. Jaime; Serra-Silva, S.; Evangelia Kartsounidou (Political representation in Southern Europe and Latin America. Before and After the Great Recession and the Commodity Crisis., 2020)
André Freire, Xavier Coller, Ioannis Andreadis, Antonio M. Jaime, Sofia Serra da Silva, & Evangelia Kartsounidou (2020), «Methodological challenges in the study of political elites. Some reflections from Southern Europe», in André Freire, Mélany Barragan, Xavier Coler, Marco Lisi & Emmanouil Tsatsanis (editors) (2020), Political representation in Southern Europe and Latin America. Before and After the Great Recession and the Commodity Crisis., Edited volume for Routledge book series “Routledge Research on Social and Political Elites”, 2020.